Infinity gate - Carey, M. R., 1959- (Carey, M. R., 1959- Pandominion, 2023)
"The Pandominion: a political and trading alliance of a million worlds. Except that they're really just one world, Earth, in many different realities. And when an A.I. threat arises that could destroy everything the Pandominion has built, they'll eradicate it by whatever means necessary. Scientist Hadiz Tambuwal is looking for a solution to her own Earth's environmental collapse when she stumbles across the secret of inter-dimensional travel, a secret that could save everyone on her dying planet. It leads her into the middle of a war on a scale she never dreamed of. And she needs to choose a side before every reality pays the price."--Provided by publisher.